1999
DOI: 10.1557/s1092578300002908
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Lateral Overgrowth of GaN with Chloride-Based Growth Chemistries in Both Hydride and Metalorganic Vapor Phase Epitaxy

Abstract: Epitaxial lateral overgrowth (ELO) of GaN on SiO 2 -masked (0001) GaN substrates has been investigated by using chloride-based growth chemistries via hydride vapor phase epitaxy (HVPE) and metal organic vapor phase epitaxy (MOVPE). Diethyl gallium chloride, (C 2 H 5 ) 2 GaCl, was used in as the MOVPE Ga precursor. The lateral and vertical growth rates as well as the overgrowth morphology of ELO GaN structures are dependent on growth temperature, V/III ratio and the in-plane orientation of the mask opening. A h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Therefore the basic features described in Section 3.2.1 are observed [102,103]. This alternative method might be interesting for achieving high growth rates.…”
Section: (C 2 H 5 ) 2 Gacl As Ga Sourcementioning
confidence: 99%
“…Therefore the basic features described in Section 3.2.1 are observed [102,103]. This alternative method might be interesting for achieving high growth rates.…”
Section: (C 2 H 5 ) 2 Gacl As Ga Sourcementioning
confidence: 99%
“…For example, the experimental work of Li et al [20] demonstrated that the carrier gas composition (H 2 /N 2 ) in combination with the polarity of the GaN facets enhanced the formation of 1100 vertical sidewalls in submicrometer GaN rods. Only a few investigations have been made by SAG-HVPE: (i) Wang et al [21] have reported the influence of the growth temperature and reactor pressure on crack density in thick layers and (ii) Zhang et al [22] have proved that both the growth rate and the shape of GaN prisms were dependent on the growth conditions and on the orientation of the window opening.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers on the MOVPE process have reported the crystallographic morphology dependence on the growth temperature, the fill factor and the V/III ratio [22][23][24][25] whatever the stripe orientations /1 1 À2 0S or /1 À 1 0 0S on GaN templates. Hiramatsu et al [26] have observed that the stripe shape along the /1 1 À 2 0S direction was limited by N-polar {1 À 1 0 1} pyramid facets and did not depend on the partial pressures and the growth temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This was ascribed to surface energy and facets stability considerations. The influence of the growth temperature and the V/III ratio on the lateral and vertical growth rates was clearly discussed [22][23][24][25]. MOVPE Facet Controlled Epitaxial Lateral Overgrowth (FACELO) technique was also developed [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation